Neodymium-iron-boron coarse powder, neodymium-iron-boron permanent magnet, and preparation method and use thereof

CN122889539APending Publication Date: 2026-10-09JL MAG RARE EARTH (BAOTOU) CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611364380.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

该方法所得磁体的矫顽力仍较低

Benefits of technology

[0019]本发明的钕铁硼粗粉的制备方法通过吸氢-脱氢的步骤,实现了富钕相的重构和润湿;通过控制再吸氢的过程吸氢后不脱氢的步骤实现了主相晶界的解离。这样的制备方法有利于减少穿晶缺陷,提升制粉速率,提高压型取向度,降低磁体的杂质元素的含量,有利于稀土元素的均匀渗透,从而有利于提高钕铁硼永磁体的综合磁性能。本发明的钕铁硼永磁体的制备方法能够保证高剩磁的同时显著提升矫顽力,且磁体的碳、氧、氮含量显著降低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889539A_ABST
    Figure CN122889539A_ABST
Patent Text Reader

Abstract

The application discloses a neodymium-iron-boron coarse powder, a preparation method and application thereof. The method comprises the following steps: (1) hydrogen absorption of neodymium-iron-boron alloy sheet, hydrogen desorption after saturation, and initial coarse powder is obtained; (2) re-hydrogen absorption of the initial coarse powder, and the neodymium-iron-boron coarse powder is obtained without hydrogen desorption after re-hydrogen absorption; wherein, the hydrogen content of the initial coarse powder is 500-1300 ppm; the hydrogen content of the obtained neodymium-iron-boron coarse powder is 1200-2200 ppm. The obtained neodymium-iron-boron coarse powder is conducive to improving the magnetic properties of the neodymium-iron-boron permanent magnet. The application further discloses a neodymium-iron-boron permanent magnet and a preparation method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a neodymium iron boron coarse powder, a neodymium iron boron permanent magnet, its preparation method, and its uses. Background Technology

[0002] Sintered neodymium iron boron (NdFeB) magnets are widely used in new energy vehicles, wind power generation, and consumer electronics due to their excellent magnetic properties. As downstream applications place increasingly higher demands on magnet performance, the challenge lies in ensuring high remanence (…). Br While significantly improving coercivity () Hcj This has become a research focus in the field.

[0003] In the current sintering process of NdFeB, hydrogen breakage (HD) is a crucial step. The principle is that rare-earth intermetallic compounds absorb hydrogen, causing lattice expansion and generating intergranular cracks, thus breaking the cast sheet. Currently, the mainstream process in the industry mostly adopts a "hydrogen absorption-dehydrogenation" method: first, hydrogen is absorbed for breakage, followed by high-temperature dehydrogenation to obtain low-hydrogen coarse powder. This may result in excessively low hydrogen content (e.g., complete dehydrogenation), leading to fewer intergranular cracks, low breakage efficiency, and excessively large and irregularly shaped coarse powder particles. Simultaneously, the final magnet has a high content of non-metallic impurities such as carbon, oxygen, and nitrogen. Furthermore, the high impurity element content and poor grain boundary wettability of the low-hydrogen coarse powder result in high penetration resistance and insufficient diffusion depth during grain boundary diffusion treatment, making it difficult to obtain high coercivity. On the other hand, excessively high hydrogen content in the coarse powder (>2200 ppm) leads to poor orientation of the magnetic powder during the molding and orientation process, resulting in reduced remanence of the sintered magnet.

[0004] CN114284020A discloses a method for hydrogen-breaking NdFeB alloys and a method for preparing NdFeB magnets. The method involves first absorbing hydrogen from the NdFeB alloy, followed by a first dehydrogenation, and then cooling to obtain pre-hydrogenated NdFeB with a hydrogen content of 1800 ppm or higher. The pre-hydrogenated NdFeB is then subjected to a second hydrogen absorption, followed by a second dehydrogenation, and then cooled to obtain coarse NdFeB powder. The hydrogen content of the coarse NdFeB powder obtained by this method is less than or equal to 1000 ppm, achieving improved coercivity of the NdFeB magnet without significant change in remanence, although the coercivity of the magnet remains relatively low.

[0005] CN119132820A discloses a method for preparing high-remanence NdFeB magnets. This method involves hydrogen crushing without dehydrogenation, resulting in a high-hydrogen-content coarse powder with a hydrogen content of 1500–3500 ppm. This high-hydrogen-content coarse powder is then subjected to air jet milling, orientation pressing, and sintering to obtain the high-remanence NdFeB magnet. This method improves the remanence of the NdFeB magnet, but the coercivity of the magnet does not change significantly.

[0006] CN121460321A discloses a low-carbon, high-purity NdFeB magnet and its preparation method. The method involves hydrogen crushing and low-temperature dehydrogenation at 50–200℃ to obtain coarse powder with a hydrogen content greater than 2000 ppm. This powder is then mixed with a lubricant and antioxidant, air-milled, magnetically oriented, pressed, sintered, and aged to obtain the magnet. However, the magnet obtained by this method still exhibits relatively low coercivity. Summary of the Invention

[0007] In view of this, one object of the present invention is to provide a method for preparing NdFeB coarse powder. The NdFeB coarse powder obtained by this method can ensure high remanence of NdFeB permanent magnets while improving the coercivity of the magnets, and can also reduce the carbon, oxygen, and nitrogen content of NdFeB permanent magnets. Another object of the present invention is to provide NdFeB coarse powder prepared by the preparation method described above. A further object of the present invention is to provide the use of NdFeB coarse powder prepared by the preparation method described above or the NdFeB coarse powder described above. Yet another object of the present invention is to improve a method for preparing NdFeB permanent magnets. This method can significantly improve coercivity while ensuring high remanence, and can also reduce the carbon, oxygen, and nitrogen content of NdFeB permanent magnets. A further object of the present invention is to provide a NdFeB permanent magnet prepared by the preparation method described above. This NdFeB permanent magnet has high remanence and coercivity, and also has low carbon, oxygen, and nitrogen content.

[0008] The present invention achieves the above objectives using the following technical solutions.

[0009] On the one hand, the present invention provides a method for preparing neodymium iron boron coarse powder, comprising the following steps: (1) absorbing hydrogen into a neodymium iron boron alloy sheet, and then dehydrogenating it after hydrogen absorption saturation to obtain initial coarse powder; (2) The initial coarse powder is subjected to hydrogen reabsorption, and no dehydrogenation is performed after the hydrogen reabsorption to obtain NdFeB coarse powder; The initial coarse powder has a hydrogen content of 500–1300 ppm; the resulting NdFeB coarse powder has a hydrogen content of 1200–2200 ppm.

[0010] According to the preparation method of the present invention, preferably, in step (1), the neodymium iron boron alloy sheet is subjected to hydrogen absorption under a first hydrogen pressure in the furnace, wherein the first hydrogen pressure in the furnace is greater than 80 kPa and less than or equal to 130 kPa; the thickness of the neodymium iron boron alloy sheet is 0.18 to 0.42 mm; the dehydrogenation temperature is 520 to 650 °C, and the vacuum degree in the furnace after dehydrogenation is less than or equal to 100 Pa; In step (2), the initial coarse powder is re-absorbed with hydrogen under the second hydrogen pressure in the furnace, wherein the second hydrogen pressure in the furnace is greater than 50 kPa and less than or equal to 80 kPa; the vacuum degree in the furnace during re-absorption of hydrogen is less than or equal to 1500 Pa.

[0011] According to the preparation method of the present invention, preferably, the hydrogen content of the obtained NdFeB coarse powder is 1500-2150 ppm; and the particle size of the obtained NdFeB coarse powder is 100-1500 μm.

[0012] According to the preparation method of the present invention, preferably, the NdFeB alloy sheet is obtained by melting and spinning various raw materials, and the composition of the NdFeB alloy sheet is RE x M y B z Fe bal RE is selected from one or more of La, Pr, Nd, Y, Ho, Dy, Gd, Tb, and Er, and must contain Nd; M is selected from one or more of Co, Al, Cu, Zr, Ga, Nb, Ta, and Ti. Where x, y, and z represent the weight parts of RE, M, and B, respectively, and bal represents the balance, which consists of Fe and unavoidable impurities; based on 100 parts by weight of NdFeB alloy sheet, 28≤x≤35, 0.75≤y≤1.1, and 0.8≤z≤1.1.

[0013] On the other hand, the present invention provides a neodymium iron boron coarse powder, which is prepared by the preparation method described above.

[0014] In another aspect, the present invention provides the use of NdFeB coarse powder prepared by the preparation method described above, or NdFeB coarse powder prepared as described above, in improving the remanence and / or coercivity of NdFeB permanent magnets.

[0015] In another aspect, the present invention provides a method for preparing neodymium iron boron permanent magnets, comprising the following steps: 1) subjecting the neodymium iron boron coarse powder as described above to air jet milling to obtain neodymium iron boron fine powder; 2) The NdFeB fine powder is pressed in an orientation magnetic field to obtain a NdFeB compact; 3) Sinter and age the NdFeB compact to obtain sintered NdFeB magnets; 4) The sintered NdFeB magnets are infiltrated with Tb or Dy to obtain NdFeB permanent magnets.

[0016] According to the preparation method of the present invention, preferably, it includes the following specific steps: 1) Under a protective atmosphere, the NdFeB coarse powder as described above is mixed with an antioxidant and then subjected to an air jet mill to obtain NdFeB fine powder; wherein, the amount of the antioxidant is 0.08-0.25% of the mass of the NdFeB coarse powder; the air jet mill speed is 178-244 kg / h; and the average particle size D of the NdFeB fine powder is... 50 It is 2–5 μm; 2) Stir the NdFeB fine powder and lubricant through a 60-150 mesh sieve to obtain a mixture; wherein, the amount of lubricant is 0.05-0.3% of the mass of the NdFeB fine powder; press the mixture under a magnetic field strength of 1.5-3T to obtain a NdFeB compact; 3) Sinter the NdFeB compact at 1050-1090℃ for 3-8 hours, and then sinter at 1060-1080℃ for 2-12 hours to obtain a sintered body; subject the sintered body to two-stage aging treatment to obtain a sintered NdFeB magnet.

[0017] According to the preparation method of the present invention, preferably, in step 3), the first aging temperature is 720-950℃ and the first aging time is 1-6h; the second aging temperature is 450-600℃ and the second aging time is 1-6h; in step 4), Tb or Dy is screen-printed onto the surface of the sintered NdFeB magnet, then infiltrated at 800-1000℃ for 10-20h, and then aged at 400-600℃ for 5-15h to obtain the NdFeB permanent magnet.

[0018] In another aspect, the present invention provides a neodymium iron boron permanent magnet prepared by the preparation method described above.

[0019] The method for preparing NdFeB coarse powder of the present invention achieves the reconstruction and wetting of the NdFeB-rich phase through a hydrogen absorption-dehydrogenation step; and achieves the dissociation of the main phase grain boundaries by controlling the hydrogen absorption process without dehydrogenation after hydrogen absorption. This preparation method is beneficial for reducing transgranular defects, increasing the powdering rate, improving the molding orientation, reducing the content of impurity elements in the magnet, and promoting the uniform penetration of rare earth elements, thereby improving the overall magnetic properties of the NdFeB permanent magnet. The method for preparing NdFeB permanent magnets of the present invention can significantly improve coercivity while ensuring high remanence, and significantly reduce the carbon, oxygen, and nitrogen content of the magnet. Attached Figure Description

[0020] Figure 1 This is a schematic SEM image of the microstructure of the NdFeB coarse powder in Example 1.

[0021] Figure 2 This is a schematic SEM image of the microstructure of the neodymium iron boron fine powder in Example 1.

[0022] Figure 3 This is a schematic SEM image of the cross-sectional morphology of the sintered NdFeB magnet in Example 1.

[0023] Figure 4 This is a schematic SEM image of the microstructure of the NdFeB coarse powder in Comparative Example 2.

[0024] Figure 5 This is a schematic diagram of the microstructure of the NdFeB fine powder in Comparative Example 2 using SEM.

[0025] Figure 6 This is a schematic SEM image of the cross-sectional morphology of the sintered NdFeB magnet in Comparative Example 2. Detailed Implementation

[0026] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0027] The "remanence" mentioned in this invention refers to the magnetic flux density at the point where the magnetic field strength on the saturation hysteresis loop is zero, usually denoted as Br or Mr The unit is Tesla (T) or Gauss (Gs). 1 Gs = 0.0001 T.

[0028] The "coercivity" mentioned in this invention refers to "intrinsic coercivity," which means that when a magnet is in a saturated magnetization state, if the magnetic field is monotonically decreased until it becomes zero and then increased in the opposite direction, the magnetic field strength corresponding to the decrease in magnetization intensity to zero along the saturation hysteresis loop is the coercivity, usually denoted as . Hcj or MHc The unit is ozt (Oe) or ampere per meter (A / m). 1 Oe = 79.6 A / m.

[0029] The "thickness distribution rate" mentioned in this invention refers to the proportion of the number of samples within a specified thickness range to the total number of samples measured in a certain thickness measurement sample.

[0030] The "nucleation point density" mentioned in this invention refers to the number density of crystal nuclei formed during the cooling of the alloy melt in the rapid quenching or casting process. The calculation formula is ρ=N / A (nuclei / mm²). 2 ), where N represents the number of nucleation points within the observation area; A represents the area of ​​the observation area.

[0031] The "protective atmosphere" described in this invention refers to an atmosphere that does not react with the magnet and does not affect its magnetic properties. In this invention, the "protective atmosphere" can be an atmosphere formed by nitrogen or an inert gas (helium, neon, argon, krypton, xenon).

[0032] The "average particle size D" described in this invention 50 “” indicates the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 50%.

[0033] The "hydrogen saturation" described in this invention involves placing a NdFeB alloy in a hydrogen atmosphere, where the NdFeB-rich grain boundary phase and the main phase undergo a hydrogenation reaction, accompanied by lattice expansion that causes the alloy to crack; hydrogen saturation is achieved when the hydrogen pressure in the furnace no longer decreases significantly.

[0034] Preparation method of NdFeB coarse powder The method for preparing NdFeB coarse powder of the present invention includes the following steps: (1) a hydrogen absorption and dehydrogenation step; (2) a hydrogen absorption step followed by no dehydrogenation. Preferably, it further includes a step of preparing NdFeB alloy sheets.

[0035] This invention obtains NdFeB coarse powder through a series of hydrogen absorption-dehydrogenation-re-hydrogen absorption steps. The inventors believe that hydrogen absorption and dehydrogenation promote the formation of a more continuous and uniform thin layer of the NdFeB-rich phase at the grain boundaries, laying the microstructural foundation for the re-hydrogen absorption process. The re-hydrogen absorption process, without subsequent dehydrogenation, employs a controlled hydrogen absorption method to enhance the uniformity and interfacial activity of the NdFeB-rich phase and lower the energy barrier for grain boundary diffusion. By controlling the pressure, time, and vacuum level of the re-hydrogen absorption, the hydrogen content of the resulting NdFeB coarse powder is kept within the range specified in this invention. This facilitates obtaining NdFeB coarse powder with uniform particle size, increases the powdering rate, and improves the penetration efficiency and uniformity of rare earth elements, thereby effectively improving the magnetic properties of NdFeB permanent magnets, especially significantly increasing coercivity and effectively reducing the amount of heavy rare earth elements required. Simultaneously, it also helps reduce oxidation reactions and decrease the impurity content of the magnet. In summary, the method for preparing NdFeB coarse powder of the present invention can achieve precise control over the micromorphology and phase composition of grain boundaries, thereby effectively improving the coercivity of NdFeB permanent magnets.

[0036] The following is a detailed description.

[0037] Steps for preparing NdFeB alloy sheets The neodymium iron boron alloy sheet of the present invention is obtained by melting and spinning various raw materials.

[0038] In this invention, raw materials are melted in a vacuum rapid solidification casting furnace to obtain an alloy mother liquor. To prevent oxidation of the raw materials and the alloy mother liquor, the melting is preferably carried out under a vacuum or protective atmosphere. The melting temperature of this invention can be 1100–1600°C, preferably 1400–1480°C. The alloy mother liquor is then processed using a rapid solidification and spinning process to produce NdFeB alloy sheets.

[0039] Raw materials are provided according to the chemical composition of NdFeB alloy sheets. The composition of the NdFeB alloy sheets is RE... x M y B z Fe bal .

[0040] RE is selected from one or more of La, Pr, Nd, Y, Ho, Dy, Gd, Tb, and Er, and must contain Nd. Preferably, it is selected from one or more of La, Pr, Nd, and Y, and must contain Nd. More preferably, it is selected from one or more of Pr and Nd, and must contain Nd. According to one embodiment of the present invention, RE is Pr and Nd, where Pr is praseodymium and Nd is neodymium. The mass ratio of the two is 1:3 to 4.

[0041] Based on 100 parts by weight of NdFeB alloy sheet, RE is x parts by weight, 28≤x≤35; preferably, 29≤x≤33; more preferably, 29.5≤x≤31.5. For example, x can be 29.5, 29.6, 29.7, 29.8, 29.9, 30.0, 30.3, 30.5, 31.0, or 31.5. This is beneficial for improving the uniformity and interfacial activity of the NdFeB coarse powder's NdFeB phase, increasing element penetration efficiency and uniformity, thereby further improving the magnet's coercivity.

[0042] M is selected from one or more of Co, Al, Cu, Zr, Ga, Nb, Ta, and Ti. Preferably, it is selected from one or more of Cu, Zr, Ga, Nb, Co, Al, and Ti. More preferably, it is selected from one or more of Cu, Zr, Ga, Nb, and Ti. Cu is copper, Zr is zirconium, Ga is gallium, Nb is niobium, and Ti is titanium. Based on 100 parts by weight of NdFeB alloy sheet, M is y parts by weight, 0.75≤y≤1.1; preferably, 0.80≤y≤0.95; more preferably, 0.82≤x≤0.93.

[0043] According to one embodiment of the present invention, M is Cu, Zr, Ga, Nb, and Ti. Based on 100 parts by weight of NdFeB alloy sheet, Cu is 0.1 to 0.5 parts by weight; preferably 0.15 to 0.43 parts by weight; more preferably 0.20 to 0.35 parts by weight; and even more preferably 0.22 to 0.32 parts by weight. For example, Cu can be 0.22 parts by weight, 0.23 parts by weight, 0.24 parts by weight, 0.25 parts by weight, 0.26 parts by weight, 0.27 parts by weight, 0.28 parts by weight, 0.29 parts by weight, 0.30 parts by weight, 0.31 parts by weight, or 0.32 parts by weight.

[0044] Based on 100 parts by weight of NdFeB alloy sheet, Zr is 0.01 to 0.35 parts by weight; preferably 0.05 to 0.30 parts by weight; more preferably 0.07 to 0.25 parts by weight; and even more preferably 0.08 to 0.15 parts by weight. For example, Zr can be 0.08 parts by weight, 0.09 parts by weight, 0.10 parts by weight, 0.11 parts by weight, 0.12 parts by weight, 0.13 parts by weight, 0.14 parts by weight, or 0.15 parts by weight.

[0045] Based on 100 parts by weight of NdFeB alloy sheet, Ga is 0.1 to 0.5 parts by weight; preferably 0.15 to 0.43 parts by weight; more preferably 0.17 to 0.35 parts by weight; and even more preferably 0.17 to 0.25 parts by weight. For example, Ga can be 0.17 parts by weight, 0.18 parts by weight, 0.19 parts by weight, 0.20 parts by weight, 0.21 parts by weight, 0.22 parts by weight, 0.23 parts by weight, 0.24 parts by weight, or 0.25 parts by weight.

[0046] Based on 100 parts by weight of NdFeB alloy sheet, Nb is 0.05 to 0.35 parts by weight; preferably 0.1 to 0.3 parts by weight; more preferably 0.12 to 0.25 parts by weight; and even more preferably 0.13 to 0.20 parts by weight. For example, Nb can be 0.13 parts by weight, 0.14 parts by weight, 0.15 parts by weight, 0.16 parts by weight, 0.17 parts by weight, 0.18 parts by weight, 0.19 parts by weight, or 0.20 parts by weight.

[0047] Based on 100 parts by weight of NdFeB alloy sheet, Ti is 0.05 to 0.35 parts by weight; preferably 0.1 to 0.3 parts by weight; more preferably 0.12 to 0.25 parts by weight; and even more preferably 0.13 to 0.20 parts by weight. For example, Ti can be 0.13 parts by weight, 0.14 parts by weight, 0.15 parts by weight, 0.16 parts by weight, 0.17 parts by weight, 0.18 parts by weight, 0.19 parts by weight, or 0.20 parts by weight.

[0048] According to a preferred embodiment of the present invention, M is Zr, Ti, Ga, Cu, and Nb, based on 100 parts by weight of NdFeB alloy sheet, where Zr is 0.09–0.11 parts by weight, Ti is 0.14–0.16 parts by weight, Ga is 0.19–0.21 parts by weight, Cu is 0.24–0.26 parts by weight, and Nb is 0.14–0.16 parts by weight. This composition of M is beneficial for improving the uniformity and interfacial activity of the NdFeB coarse powder, increasing the penetration efficiency and uniformity of heavy rare earth elements during grain boundary diffusion, thereby further improving the coercivity of the magnet.

[0049] B represents boron. Based on 100 parts by weight of NdFeB alloy sheet, 0.8 ≤ z ≤ 1.1; preferably, 0.90 ≤ z ≤ 1.05; more preferably, 0.92 ≤ z ≤ 1.02. For example, B can be 0.92 parts by weight, 0.93 parts by weight, 0.94 parts by weight, 0.95 parts by weight, 0.96 parts by weight, 0.97 parts by weight, 0.98 parts by weight, 0.99 parts by weight, 1.00 parts by weight, 1.01 parts by weight, or 1.02 parts by weight.

[0050] Fe represents iron. Bal is the balance, referring to the Fe content of (100-xyz) parts by weight based on 100 parts by weight of NdFeB alloy sheet. Unless otherwise stated, all parts mentioned in this invention refer to parts by weight.

[0051] In one embodiment of the present invention, based on 100 parts by weight of a NdFeB alloy sheet, RE is x parts by weight, where x is 29-31, and RE consists of Pr and Nd in a weight ratio of 1:3; M comprises only Zr, Ti, Ga, Cu, and Nb, where Zr is 0.09-0.11 parts by weight, Ti is 0.14-0.16 parts by weight, Ga is 0.19-0.21 parts by weight, Cu is 0.24-0.26 parts by weight, and Nb is 0.14-0.16 parts by weight; B is y parts by weight, where y is 0.94-0.96 parts by weight; and Fe is the balance. The coarse powder obtained from such a NdFeB alloy sheet has a uniform particle size distribution and a uniform crystalline phase distribution, which is beneficial for the penetration of heavy rare earth elements during grain boundary diffusion, resulting in high and uniform penetration efficiency of heavy rare earth elements. This is beneficial for improving the coercivity of the magnet.

[0052] The raw materials for the NdFeB alloy sheet of this invention can be pure elemental substances or intermediate alloys containing the elements; this invention does not impose any particular limitation. The purity of the pure elemental substances or intermediate alloys must be at least 99.99% or higher. All raw materials for the NdFeB alloy sheet of this invention are commercially available. The amount of each raw material used is matched to the mass proportion of each component in the expected NdFeB alloy sheet.

[0053] The thickness of the neodymium iron boron alloy sheet can be 0.18–0.42 mm; preferably 0.20–0.30 mm; more preferably 0.22–0.27 mm.

[0054] The thickness distribution of the NdFeB alloy sheet of the present invention is as follows: Thickness 0-0.10 mm, accounting for 0-1%; preferably, 0.2-0.8%; more preferably, 0.4-0.6%. Thickness 0.10-0.15 mm, accounting for 5-10%; preferably, 6-9%; more preferably, 7-8%. Thickness 0.15-0.20 mm, accounting for 5-15%; preferably, 8-12%; more preferably, 9-11%. Thickness 0.20-0.25 mm, accounting for 10-20%; preferably, 12-18%; more preferably, 14-17%. Thickness 0.25-0.30 mm, accounting for 70-85%; preferably, 75-82%; more preferably, 77-79%. The thickness is 0.30–0.35 mm, accounting for 3–5%; preferably, 3.5–4.5%; more preferably, 3.8–4.2%. The thickness is 0.35–0.42 mm, accounting for 1–3%; preferably, 1.5–2.5%; more preferably, 1.8–3.2%. The thickness is greater than 0.42 mm; accounting for less than 1%; preferably, less than 0.8%; more preferably, less than or equal to 0.5%.

[0055] The nucleation point density of the neodymium iron boron alloy sheet of the present invention can be 80 to 250 nucleation points / mm. 2 Preferably, the number of particles per mm is 130–220. 2 More preferably, 150–190 pieces / mm 2 Such NdFeB alloy sheets are advantageous for obtaining NdFeB coarse powder with uniform particle size.

[0056] The steps of hydrogen absorption and dehydrogenation The neodymium iron boron alloy sheet is subjected to hydrogen absorption, and after hydrogen saturation, it is dehydrogenated to obtain the initial coarse powder.

[0057] In this invention, neodymium iron boron alloy sheets are subjected to hydrogen absorption under a first hydrogen pressure inside the furnace. The first hydrogen absorption pressure inside the furnace is greater than 80 kPa and less than or equal to 130 kPa; preferably, it is greater than 90 kPa and less than or equal to 100 kPa; more preferably, it is greater than 95 kPa and less than or equal to 99 kPa.

[0058] During hydrogen absorption, the furnace chamber is rotated 10–30 times, preferably 15–20 times. More preferably, it is rotated 16–18 times. Each rotation lasts 1–8 minutes, preferably 3–6 minutes. More preferably, it is 4–5 minutes. After each rotation, the furnace is stopped for 1–10 minutes, preferably 3–7 minutes. More preferably, it is 4–6 minutes. These hydrogen absorption conditions are beneficial for obtaining NdFeB coarse powder with uniform particle size.

[0059] The dehydrogenation temperature of this invention is 520–650°C; preferably 555–605°C; more preferably 550–600°C; and even more preferably 575–595°C. The dehydrogenation time is 1–5 hours; preferably 3–4.5 hours; and more preferably 3.5–4 hours. This improves the dehydrogenation efficiency, ensures the dehydrogenation effect, and keeps the hydrogen content of the initial coarse powder within the range specified in this invention.

[0060] The vacuum level inside the furnace after dehydrogenation is less than or equal to 100 Pa. Preferably, it is less than or equal to 80 Pa. More preferably, it is less than or equal to 75 Pa.

[0061] In this invention, the relationship between the vacuum level inside the furnace after dehydrogenation and the weight of the NdFeB alloy sheet is as follows: when the weight of the NdFeB alloy is <150kg, the vacuum level is ≤40Pa; when the weight of the NdFeB alloy is 150kg ≤ 900kg, the vacuum level is ≤45Pa; when the weight of the NdFeB alloy is 900kg ≤ 1500kg, the vacuum level is ≤55Pa; when the weight of the NdFeB alloy is 1500kg ≤ 2500kg, the vacuum level is ≤65Pa; and when the weight of the NdFeB alloy is ≥2500kg, the vacuum level is ≤75Pa. This is beneficial for improving dehydrogenation efficiency and ensuring the dehydrogenation effect.

[0062] In this invention, the hydrogen content of the initial coarse powder is 500-1300 ppm; preferably 550-1200 ppm; more preferably 600-1000 ppm; and even more preferably 590-810 ppm.

[0063] The step of re-absorbing hydrogen without dehydrogenation. The initial coarse powder is subjected to hydrogen reabsorption, and no dehydrogenation is performed after the reabsorption to obtain NdFeB coarse powder.

[0064] The hydrogen content of the obtained NdFeB coarse powder is 1200–2200 ppm; preferably 1500–2150 ppm; more preferably 1900–2100 ppm. The average particle size D of the NdFeB coarse powder is... 50 The micrometer size is 100–1500 μm; preferably 200–800 μm; more preferably 350–600 μm; and even more preferably 500–575 μm.

[0065] In this invention, the initial coarse powder is subjected to re-hydrogen absorption under a second hydrogen pressure inside the furnace. The second hydrogen absorption pressure inside the furnace is greater than 50 kPa and less than or equal to 80 kPa; preferably, it is greater than 63 kPa and less than or equal to 79 kPa; more preferably, it is greater than 67 kPa and less than or equal to 75 kPa.

[0066] During hydrogen reabsorption, the furnace chamber is rotated 8 to 25 times; preferably, 12 to 19 times; more preferably, 14 to 18 times. For example, it can be 14, 15, 16, 17, or 18 times. Each rotation lasts 1 to 5 minutes; preferably 2 to 4 minutes; more preferably 2.5 to 3.5 minutes. The stop time is 1 to 6 minutes; preferably 2 to 5 minutes; more preferably 3 to 4 minutes. Such hydrogen reabsorption conditions can control the hydrogen content of the NdFeB coarse powder within the range of this invention, thereby obtaining NdFeB coarse powder with uniform particle size, increasing the powdering rate, and further improving the element penetration efficiency and penetration uniformity, which is beneficial to improving the magnetic properties of NdFeB permanent magnets, especially significantly improving coercivity.

[0067] During hydrogen reabsorption, the vacuum level inside the furnace is less than or equal to 1500 Pa; preferably, it is greater than 890 Pa and less than or equal to 1200 Pa; more preferably, it is greater than 500 Pa and less than or equal to 890 Pa; and even more preferably, it is greater than 150 Pa and less than or equal to 500 Pa. This helps to improve the efficiency of hydrogen reabsorption and ensure the effectiveness of hydrogen reabsorption.

[0068] Neodymium iron boron coarse powder The NdFeB coarse powder of the present invention is prepared by the method described above. Such NdFeB coarse powder has a uniform particle size distribution, which is beneficial to improving the coercivity of NdFeB permanent magnets and reducing the carbon, oxygen, and nitrogen content of NdFeB permanent magnets.

[0069] Uses of NdFeB coarse powder The present invention also provides the use of NdFeB coarse powder prepared by the preparation method described above, or NdFeB coarse powder as described above, in improving the remanence and / or coercivity of NdFeB permanent magnets. In particular, its use in significantly improving coercivity while maintaining high remanence.

[0070] Preparation method of neodymium iron boron permanent magnet The method for preparing the neodymium iron boron permanent magnet of the present invention includes the following steps: air jet milling, molding, sintering and aging, and grain boundary diffusion. Each step is described in detail below.

[0071] This invention discovers that by using the NdFeB alloy sheet of this invention, combined with the specific NdFeB coarse powder preparation method of this invention, and then subjecting it to air jet milling, orientation pressing, sintering aging, and grain boundary diffusion treatment, it is possible not only to significantly improve the coercivity of the magnet while ensuring high remanence, but also to significantly reduce the carbon, oxygen, and nitrogen content of the obtained NdFeB permanent magnet, and to effectively reduce the amount of heavy rare earth elements used.

[0072] Steps of air jet mill The NdFeB coarse powder described above is subjected to air jet milling to obtain NdFeB fine powder. Specifically, under a protective atmosphere, the NdFeB coarse powder described above is mixed with an antioxidant and then subjected to air jet milling to obtain NdFeB fine powder.

[0073] In this invention, the amount of antioxidant can be 0.08-0.25% of the mass of NdFeB crude powder; preferably 0.09-0.18%; more preferably 0.095-0.13%. For example, 0.095wt%, 0.098wt%, 0.1wt%, 0.11wt%, 0.12wt%, or 0.13wt%. The antioxidant can be stearic acid, tributyl borate, methyl stearate, ethyl stearate, antioxidant 1010, methyl oleate, phosphite, or other substances known in the art, or a mixture with the above-described compounds as the main components. This invention is not limited in scope.

[0074] In some embodiments, prior to grinding with an air jet mill, the NdFeB coarse powder is transferred to a container under an argon atmosphere. A protective atmosphere is then introduced into the container for 5–20 seconds until the pressure reaches 0.01–0.07 MPa. High-purity nitrogen is preferably used as the protective atmosphere. The size of the container should be matched to the weight of the NdFeB coarse powder.

[0075] The air jet milling rate of the present invention can be 178–244 kg / h; preferably 180–240 kg / h; more preferably 185–237 kg / h. This is beneficial for reducing the average particle size D of the NdFeB fine powder. 50 Within the scope of this invention, the powdering efficiency can also be improved.

[0076] The average particle size D of the obtained NdFeB fine powder 50 The particle size is 2–5 μm; preferably 3–4 μm; more preferably 3.1–3.4 μm. Such fine NdFeB powder is more conducive to improving the coercivity of NdFeB permanent magnets and reducing the carbon, oxygen, and nitrogen content.

[0077] In this invention, the average particle size D of the obtained NdFeB fine powder is... 50 When the value is within ±0.1μm of the process error centered on the target particle size, it is considered to have the same particle size level.

[0078] molding steps Neodymium iron boron powder is pressed in an orientation magnetic field to obtain neodymium iron boron compacts.

[0079] In this invention, NdFeB fine powder and lubricant are stirred and passed through a 60-150 mesh sieve to obtain a mixture. The amount of lubricant used can be 0.05-0.3% of the mass of the NdFeB fine powder; preferably 0.08-0.25%; more preferably 0.11-0.23%. Examples include 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt%, 0.15wt%, 0.16wt%, 0.17wt%, 0.18wt%, 0.19wt%, 0.2wt%, 0.21wt%, 0.22wt%, and 0.23wt%. The lubricant can be stearic acid, paraffin wax, butyl stearate, tributyl borate, polyethylene wax, oleamide, zinc stearate, etc., or a mixture with the above compounds as the main components. This invention does not limit the specific components.

[0080] The stirring time for neodymium iron boron fine powder and lubricant can be 90-180 min; preferably 105-130 min; more preferably 115-125 min. Then it is passed through a 60-150 mesh sieve; preferably, through an 80-120 mesh sieve; more preferably, through a 90-105 mesh sieve.

[0081] According to a specific embodiment of the present invention, the mixture is pressed under a magnetic field strength of 1.5 to 3T to obtain a neodymium iron boron compact.

[0082] The magnetic field strength can be 1.5–3 T; preferably 1.5–2.5 T; more preferably 1.7–2 T. The density of the NdFeB compact can be 2.0–6.0 g / cm³. 3 Preferably, the concentration is 2.5–5.510 g / cm³. 3 More preferably, it is 3.5–4.5 g / cm³. 3 .

[0083] The molding process can be performed under vacuum conditions. The vacuum level is less than or equal to 150 ppm. Preferably, the vacuum level is less than or equal to 120 ppm. More preferably, the vacuum level is less than or equal to 100 ppm.

[0084] Sintering and aging steps Sintered NdFeB magnets are obtained by sintering and aging NdFeB compacts.

[0085] In this invention, the neodymium iron boron compact is sintered at a first sintering temperature for 3 to 8 hours, and then sintered at a second sintering temperature for 2 to 12 hours to obtain a sintered body.

[0086] The first sintering temperature can be 1050–1090℃; preferably 1065–1085℃; more preferably 1075–1082℃. The first sintering time can be 3–8 hours; preferably 4–7 hours; more preferably 5–6 hours.

[0087] The second sintering temperature can be 1060–1080℃; preferably 1065–1075℃; more preferably 1068–1072℃. The second sintering time can be 2–12 h; preferably 4–8 h; more preferably 5–7 h.

[0088] The sintered body is subjected to a two-stage aging treatment to obtain sintered NdFeB magnets. The two-stage aging includes primary aging and secondary aging. In this invention, the primary aging temperature can be 720–950℃; preferably 800–930℃; more preferably 850–900℃. The primary aging treatment time can be 1–6 hours; preferably 2–4.5 hours; more preferably 2.5–3.5 hours. The secondary aging temperature can be 450–600℃; preferably 480–550℃; more preferably 495–525℃. The secondary aging treatment time can be 1–6 hours; preferably 2.5–5 hours; more preferably 3.5–4.5 hours.

[0089] Steps of grain boundary diffusion Sintered NdFeB magnets are infiltrated with Tb or Dy to obtain NdFeB permanent magnets.

[0090] In this invention, sintered NdFeB magnets can be made into cuboid samples by wire cutting. The thickness of the sample along the orientation direction can be 1.5 to 8 mm; preferably 3.5 to 6.5 mm; more preferably 3.8 to 5.5 mm.

[0091] In this invention, Tb or Dy can be Tb powder or Dy powder, or it can be a compound containing Tb or Dy. Compounds containing Tb or Dy include, but are not limited to, fluorides (TbF3, DyF3), oxides (Tb4O7, Tb2O3, Dy2O3), and hydrides (TbH2, DyH2). Tb or Dy can be coated onto the surface of the sintered NdFeB magnet using methods such as surface coating, vacuum evaporation, magnetron sputtering, multi-arc ion plating, and screen printing, followed by infiltration treatment at a set temperature. According to a preferred embodiment of the invention, screen printing is used to coat the surface of the sintered NdFeB magnet with Tb or Dy. The content of Tb or Dy can be 0.1–1 wt%, preferably 0.2–0.8 wt%, and more preferably 0.3–0.6 wt%. Preferably, Tb or Dy covers two opposite surfaces of the sintered NdFeB magnet in the orientation direction. This helps ensure that neodymium iron boron permanent magnets have high remanence and high coercivity.

[0092] In this invention, the permeation treatment can be carried out at a temperature of 800–1000°C; preferably, the temperature is 820–980°C; more preferably, the temperature is 850–950°C. The permeation treatment time can be 10–20 h; preferably 12–18 h; more preferably 14–16 h.

[0093] The neodymium iron boron permanent magnet is then aged at 400–600°C for 5–15 hours to obtain the magnet. The aging temperature can be 400–600°C; preferably 450–550°C; more preferably 480–520°C. The aging time can be 5–15 hours; preferably 7–13 hours; more preferably 8–12 hours. This method helps to significantly improve the coercivity of the neodymium iron boron permanent magnet while maintaining high remanence.

[0094] In this invention, the permeation treatment is performed under vacuum or a protective atmosphere. Vacuum level < 10. -2 Pa. This allows the neodymium iron boron permanent magnet to significantly improve its coercivity while maintaining high remanence.

[0095] Neodymium iron boron permanent magnet The neodymium iron boron permanent magnet of the present invention is prepared by the preparation method described above.

[0096] The neodymium iron boron permanent magnet of the present invention can significantly improve coercivity while maintaining high remanence, and can also significantly reduce the impurity content in the magnet. Compared with undiffused sintered neodymium iron boron magnets, the coercivity of the obtained neodymium iron boron permanent magnet can be increased by more than 11 kOe, and even more than 11.2 kOe.

[0097] The carbon content of the neodymium iron boron permanent magnet prepared by the method of the present invention is ≤630ppm; preferably, the carbon content is ≤595ppm; more preferably, the carbon content is ≤550ppm.

[0098] The oxygen content is ≤669ppm; preferably, the oxygen content is ≤635ppm; more preferably, the oxygen content is ≤570ppm.

[0099] The nitrogen content is ≤180ppm; preferably, the nitrogen content is ≤150ppm; more preferably, the nitrogen content is ≤130ppm; and even more preferably, the nitrogen content is ≤100ppm.

[0100] Test methods Thickness distribution: 100 NdFeB alloy samples were randomly selected, and the thickness of each sample was measured at a random point using a digital micrometer. The samples were categorized into ranges of 0–0.10 mm, 0.10–0.15 mm, 0.15–0.20 mm, 0.20–0.25 mm, 0.25–0.30 mm, 0.30–0.35 mm, 0.35–0.42 mm, and greater than 0.42 mm. The number of samples in each range was counted, and the percentage of samples in that range out of the total number of NdFeB alloy samples (100 samples) is the thickness distribution rate (%) for that range.

[0101] The average thickness (mm) of NdFeB alloy = the sum of the thicknesses of individual NdFeB alloy samples / the total number of NdFeB alloy samples (100 pieces).

[0102] Nucleation point density: The NdFeB alloy sample was mounted and fixed. The cross-section perpendicular to the roller surface of the NdFeB alloy and perpendicular to the roller mark direction was used as the polishing surface. The sample was polished to a smooth, scratch-free mirror surface. Etching was performed using a 3% nitric acid-ethanol solution. Observation was conducted using a metallographic microscope.

[0103] Scanning electron microscopy (SEM) testing: First, a conductive adhesive is attached to the sample tray of the scanning electron microscope. The sample to be tested (e.g., NdFeB coarse powder, NdFeB fine powder, or quenched NdFeB sintered blank) is then attached to the conductive adhesive. The sample surface is then sprayed with gold using an ion sputtering instrument. Finally, the morphology of the sample is analyzed using a scanning electron microscope.

[0104] Magnetic properties: Cylindrical samples were prepared using wire cutting, coreless grinding, and end-face grinding methods. The demagnetization curves of the samples were measured at 20°C using the NIM-62000 permanent magnet material magnetic property measurement system, thereby obtaining remanence and intrinsic coercivity.

[0105] Oxygen content: The oxygen content of the sample shall be tested using an oxygen-nitrogen analyzer in accordance with the provisions of XB / T 617.7.

[0106] Nitrogen content: The oxygen content of the sample shall be tested using an oxygen-nitrogen analyzer in accordance with the provisions of XB / T 617.7.

[0107] Carbon content: The carbon content of the sample shall be tested using a high-frequency infrared carbon-sulfur analyzer in accordance with the provisions of XB / T 617.6.

[0108] Preparation Example According to the composition of NdFeB alloy sheets, raw materials are fed into a vacuum rapid solidification casting furnace for melting to obtain alloy mother liquor; the alloy mother liquor is then processed using a rapid solidification and spinning process to produce NdFeB alloy sheets. Based on 100 parts by weight of NdFeB alloy sheets, the composition of the NdFeB alloy sheets is: (PrNd) 30 B 0.95 Zr 0.1 Ti 0.15 Ga 0.2 Cu 0.25 、Nb 0.15 Fe 余量 The subscript values ​​all represent parts by weight. The weight ratio of Pr to Nd is 1:3.

[0109] The average thickness of the NdFeB alloy sheet is 0.24 mm. The specific thickness distribution of the NdFeB alloy is as follows: 0–0.10 mm accounts for 0.5%, 0.10–0.15 mm accounts for 8%, 0.15–0.20 mm accounts for 10%, 0.20–0.25 mm accounts for 15%, 0.25–0.30 mm accounts for 78%, 0.30–0.35 mm accounts for 4%, 0.35–0.42 mm accounts for 2%, and greater than 0.42 mm accounts for 0.5%. The nucleation point density of the NdFeB alloy sheet is 180 nuclei / mm².

[0110] Example 1 800 kg of the neodymium iron boron alloy sheet prepared in the example was placed in a hydrogen decomposition furnace. Hydrogen gas was then introduced until the hydrogen pressure in the first furnace reached 100 kPa for hydrogen absorption. During hydrogen absorption, the furnace chamber was rotated 20 times, each rotation lasting 5 minutes, followed by a 3-minute pause, until hydrogen saturation was achieved. Then, dehydrogenation was carried out at 580℃ for 3 hours to obtain initial coarse powder. The hydrogen content of the initial coarse powder was 900 ppm. The vacuum degree inside the furnace after dehydrogenation was 42 Pa.

[0111] Then, under a vacuum of 180 Pa, hydrogen gas was introduced again into the hydrogen crushing furnace containing the initial coarse powder until the hydrogen pressure in the second furnace reached 65 kPa for re-hydrogen absorption. During re-hydrogen absorption, the furnace chamber was rotated 15 times, each rotation lasting 3 minutes followed by a 2-minute pause. No dehydrogenation was performed after the re-hydrogen absorption was completed, yielding NdFeB coarse powder. The hydrogen content of the NdFeB coarse powder was 1600 ppm, and the average particle size D of the NdFeB coarse powder was... 50 It is 515μm.

[0112] Neodymium iron boron (NdFeB) coarse powder was transferred to a 1000 kg hopper under argon protection. Nitrogen gas was introduced for 10 seconds until the pressure inside the hopper reached 0.05 MPa. Under nitrogen protection, the NdFeB coarse powder was mixed with 0.1 wt% tributyl borate and subjected to air jet milling at a rate of 188 kg / h to obtain an average particle size D. 50 It is a 3.20μm fine NdFeB powder.

[0113] Neodymium iron boron (NdFeB) fine powder and lubricant were stirred in a three-dimensional mixer for 120 minutes, and then passed through a 100-mesh sieve to obtain a mixture. The lubricant was tributyl borate, and the amount of lubricant used was 0.15% of the mass of the NdFeB fine powder. The mixture was pressed under a magnetic field strength of 1.8T and a vacuum degree ≤100ppm to obtain a density of 4.0 g / cm³. 3 Neodymium iron boron (NdFeB) blanks.

[0114] The NdFeB compact was held at 1080℃ for 6 hours, and then at 1070℃ for 6 hours to obtain a sintered body. The sintered body was then subjected to a first-stage aging treatment at 890℃ for 3 hours, and then a second-stage aging treatment at 500℃ for 4 hours to obtain a sintered NdFeB magnet.

[0115] Sintered NdFeB magnets were cut into rectangular samples with a thickness of 4 mm by wire cutting and then infiltrated with 0.5 wt% Tb. The compound containing Tb powder was screen printed onto two opposite surfaces in the orientation direction. The temperature for grain boundary diffusion was 950℃ and the holding time was 15 h. The aging temperature was 520℃ and the holding time was 5 h, thus obtaining NdFeB permanent magnets.

[0116] The SEM schematic diagram of the microstructure of the NdFeB coarse powder in this embodiment is shown below. Figure 1 As shown in the figure. A schematic SEM image of the microstructure of the NdFeB fine powder in this embodiment is shown below. Figure 2 As shown in the figure. A schematic SEM image of the cross-sectional morphology of the sintered NdFeB magnet in this embodiment is shown below. Figure 3 As shown.

[0117] Depend on Figure 1 As can be seen, the surface of the NdFeB coarse powder in this embodiment has obvious microcracks extending along the grain boundaries, and the fragmentation is uniform.

[0118] Depend on Figure 2 It can be seen that the NdFeB fine powder in this embodiment has good particle dispersion and no obvious agglomeration. Such morphology can effectively reduce the risk of abnormal grain growth during sintering, and the dispersed powder particles are more conducive to magnetic field pressing and forming, improving powder orientation and magnet remanence.

[0119] Depend on Figure 3 As can be seen, the sintered NdFeB magnet of this embodiment has small and uniformly distributed main phase grains with regular equiaxed grains and straight, clear grain boundaries, without coarse grains or abnormal grain growth. The NdFeB-rich phase is continuously and uniformly distributed at the grain boundaries, effectively isolating the main phase grains.

[0120] Example 2 Except for the following conditions, the remaining steps are the same as in Example 1.

[0121] 1500 kg of neodymium iron boron alloy sheets prepared in the example were placed in a hydrogen decomposition furnace. Hydrogen gas was then introduced into the furnace to a pressure of 99 kPa for hydrogen absorption. During hydrogen absorption, the furnace chamber was rotated 18 times, each rotation lasting 4 minutes, followed by a 4-minute pause, until hydrogen saturation was achieved. Then, dehydrogenation was carried out at 580℃ for 3.5 hours to obtain initial coarse powder. The hydrogen content of the initial coarse powder was 700 ppm. The vacuum degree inside the furnace after dehydrogenation was 60 Pa.

[0122] Then, under a vacuum of 850 Pa, hydrogen gas was introduced again into the hydrogen crusher containing the initial coarse powder until the pressure of the second hydrogen gas inside the furnace reached 70 kPa for re-hydrogen absorption. During re-hydrogen absorption, the furnace chamber was rotated 14 times, with each rotation lasting 2 minutes and followed by a 3-minute pause. No dehydrogenation was performed after the re-hydrogen absorption was completed, yielding NdFeB coarse powder. The hydrogen content of the NdFeB coarse powder was 1910 ppm, and the average particle size D of the NdFeB coarse powder was... 50 It is 535μm.

[0123] The NdFeB coarse powder was transferred to a 1500 kg hopper under argon protection. Nitrogen gas was introduced for 10 seconds until the pressure inside the hopper reached 0.05 MPa. Under nitrogen protection, the NdFeB coarse powder was mixed with 0.1 wt% tributyl borate and ground using an air jet mill at a rate of 198 kg / h to obtain an average particle size D. 50 It is a 3.18μm fine NdFeB powder.

[0124] Example 3 Except for the following conditions, the remaining steps are the same as in Example 1.

[0125] 2500 kg of neodymium iron boron alloy sheets prepared in the example were placed in a hydrogen decomposition furnace. Hydrogen gas was then introduced into the furnace to a pressure of 93 kPa for hydrogen absorption. During hydrogen absorption, the furnace chamber was rotated 16 times, each rotation lasting 4 minutes, followed by a 6-minute pause, until hydrogen saturation was achieved. Then, dehydrogenation was carried out at 580°C for 4 hours to obtain initial coarse powder. The hydrogen content of the initial coarse powder was 600 ppm. The vacuum degree inside the furnace after dehydrogenation was 66 Pa.

[0126] Then, under a vacuum of 1100 Pa, hydrogen gas was introduced again into the hydrogen crushing furnace containing the initial coarse powder until the second hydrogen pressure inside the furnace reached 78 kPa for re-hydrogen absorption. During re-hydrogen absorption, the furnace chamber was rotated 17 times, each rotation lasting 3 minutes followed by a 4-minute pause. No dehydrogenation was performed after the re-hydrogen absorption was completed, yielding NdFeB coarse powder. The hydrogen content of the NdFeB coarse powder was 2108 ppm, and the average particle size D of the NdFeB coarse powder was... 50 It is 552μm.

[0127] The NdFeB coarse powder was transferred to a 2500 kg hopper under argon protection. Nitrogen gas was introduced for 10 seconds until the pressure inside the hopper reached 0.05 MPa. Under nitrogen protection, the NdFeB coarse powder was mixed with 0.1 wt% tributyl borate and ground using an air jet mill at a rate of 235 kg / h to obtain an average particle size D. 50 It is a 3.25μm NdFeB fine powder.

[0128] Comparative Example 1 Except for the following conditions and steps, everything else is the same as in Example 1.

[0129] 800 kg of the neodymium iron boron alloy sheet prepared in the example was placed in a hydrogen decomposition furnace. Hydrogen gas was then introduced into the furnace until the initial hydrogen pressure reached 100 kPa for hydrogen absorption. During hydrogen absorption, the furnace chamber was rotated 20 times, each rotation lasting 5 minutes, followed by a 3-minute pause, until hydrogen saturation was achieved. Then, dehydrogenation was carried out at 580℃ for 2.5 hours to obtain initial coarse powder. The initial coarse powder had a hydrogen content of 1850 ppm. The vacuum degree inside the furnace after dehydrogenation was 188 Pa.

[0130] Then, under a vacuum of 180 Pa, hydrogen gas was introduced again into the hydrogen crushing furnace containing the initial coarse powder until the second hydrogen pressure inside the furnace reached 65 kPa for re-hydrogen absorption. During re-hydrogen absorption, the furnace chamber was rotated 15 times, each rotation lasting 3 minutes, followed by a 2-minute pause, until hydrogen saturation was achieved. Next, dehydrogenation was carried out at 580℃ for 2.8 hours to obtain NdFeB coarse powder. The hydrogen content of the NdFeB coarse powder was 955 ppm, and the average particle size D of the NdFeB coarse powder was... 50 The value is 580 μm. The vacuum level inside the furnace after dehydrogenation is 50 Pa.

[0131] The NdFeB coarse powder was transferred to a 1000 kg hopper under argon protection. Nitrogen gas was introduced for 10 seconds until the pressure inside the hopper reached 0.05 MPa. Under nitrogen protection, the NdFeB coarse powder was mixed with 0.1 wt% tributyl borate and ground using an air jet mill at a rate of 177 kg / h to obtain an average particle size D. 50 It is a 3.30μm fine NdFeB powder.

[0132] Comparative Example 2 Except for the following conditions and steps, everything else is the same as in Example 1.

[0133] 800 kg of the prepared NdFeB alloy sheet was placed in a hydrogen decomposition furnace, and hydrogen gas was introduced until the hydrogen pressure in the first furnace reached 100 kPa for hydrogen absorption. During hydrogen absorption, the furnace chamber was rotated 20 times, each rotation lasting 5 minutes, followed by a 3-minute pause, until hydrogen saturation was achieved. Then, dehydrogenation was carried out at 580℃ for 3 hours to obtain NdFeB coarse powder. The hydrogen content of the NdFeB coarse powder was 853 ppm, and the average particle size D of the NdFeB coarse powder was... 50 The value is 620 μm. The vacuum level inside the furnace after dehydrogenation is 43 Pa.

[0134] The NdFeB coarse powder was transferred to a 1000 kg hopper under argon protection. Nitrogen gas was introduced for 10 seconds until the pressure inside the hopper reached 0.05 MPa. Under nitrogen protection, the NdFeB coarse powder was mixed with 0.1 wt% tributyl borate and ground using an air jet mill at a rate of 174 kg / h to obtain an average particle size D. 50 It is a 3.28μm NdFeB fine powder.

[0135] The SEM image of the microstructure of the NdFeB coarse powder in this comparative example is shown below. Figure 4 As shown in the figure. A schematic SEM image of the microstructure of the NdFeB fine powder in this comparative example is shown below. Figure 5 As shown in the figure. A schematic SEM image of the cross-sectional morphology of the sintered NdFeB magnet in this comparative example is shown below. Figure 6 As shown.

[0136] Depend on Figure 4 It can be seen that the NdFeB coarse powder in this comparative example has few surface cracks and uneven fragmentation. This will affect the rate of preparing NdFeB fine powder.

[0137] Depend on Figure 5 It can be seen that the NdFeB fine powder in this comparative example contains flaky and needle-like particles, with a large amount of fine powder and obvious agglomeration.

[0138] Depend on Figure 6 It is evident that the sintered NdFeB magnets in this comparative example exhibit significant grain size variation and indistinct boundaries. The presence of coarse grains, discontinuous grain boundary phase distribution, and poor grain boundary isolation contribute to a decrease in the magnet's coercivity.

[0139] Comparative Example 3 Except for the following conditions and steps, everything else is the same as in Example 1.

[0140] 800 kg of neodymium iron boron alloy sheets prepared in the example were placed in a hydrogen crushing furnace. Hydrogen gas was then introduced until the hydrogen pressure in the first furnace reached 100 kPa for hydrogen absorption. During hydrogen absorption, the furnace chamber was rotated 20 times, each rotation lasting 5 minutes, followed by a 3-minute pause. No dehydrogenation was performed after hydrogen absorption, resulting in coarse neodymium iron boron powder. The hydrogen content of the coarse neodymium iron boron powder was 2802 ppm, and the average particle size D of the coarse neodymium iron boron powder was... 50 The average particle size was 670 μm. The NdFeB coarse powder was transferred to a 1000 kg hopper under argon protection. Nitrogen gas was introduced for 10 seconds until the pressure inside the hopper reached 0.05 MPa. Under nitrogen protection, the NdFeB coarse powder was mixed with 0.1 wt% tributyl borate and subjected to air jet milling at a rate of 245 kg / h to obtain an average particle size D. 50 It is a 3.25μm NdFeB fine powder.

[0141] The hydrogen content of the NdFeB coarse powder in Examples 1-3 and Comparative Examples 1-3 of the present invention, and the remanence of the substrate (sintered NdFeB magnet) used. Br ), intrinsic coercivity of the substrate ( Hcj The remanence of the resulting magnet (neodymium iron boron permanent magnet) Br ), intrinsic coercivity of magnets ( Hcj The carbon (C), oxygen (O), and nitrogen (N) content in the magnets are shown in Table 1.

[0142] Table 1

[0143] As shown in Table 1, compared with Comparative Examples 1 to 2, the NdFeB permanent magnets prepared in Examples 1 to 3 of the present invention exhibit higher coercivity without a significant decrease in remanence. The coercivity of the magnets is increased by more than 11 kOe, and even more than 11.2 kOe, compared with the coercivity of the substrate. Although the substrates of Comparative Examples 1 and 2 have higher coercivity, the increase in coercivity of the NdFeB permanent magnets in Examples 1, 2, and 3 of the present invention is even greater after Tb infiltration treatment. This indicates that the sintered NdFeB magnets obtained by the preparation method of the present invention, after being processed by air jet milling, pressing, sintering, and aging, are more conducive to the diffusion and infiltration of the heavy rare earth element Tb, and are more conducive to a greater increase in the coercivity of the NdFeB permanent magnets. Moreover, compared with the conventional hydrogen decomposition method (Comparative Example 2), the carbon, oxygen, and nitrogen contents of Examples 1-3 of the present invention are significantly reduced. The carbon content is below 630 ppm, the oxygen content is below 669 ppm, and the nitrogen content is below 180 ppm. In summary, the preparation method of this invention can significantly improve the coercivity while ensuring high remanence of the NdFeB permanent magnet, and can also reduce the introduction of impurities, significantly reducing the content of carbon, oxygen, and nitrogen.

[0144] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.

Claims

1. A method for preparing neodymium iron boron coarse powder, characterized in that, Includes the following steps: (1) The neodymium iron boron alloy sheet is subjected to hydrogen absorption, and after hydrogen absorption saturation, it is dehydrogenated to obtain the initial coarse powder; (2) The initial coarse powder is subjected to hydrogen reabsorption, and no dehydrogenation is performed after the hydrogen reabsorption to obtain NdFeB coarse powder; The initial coarse powder has a hydrogen content of 500–1300 ppm; the resulting NdFeB coarse powder has a hydrogen content of 1200–2200 ppm.

2. The preparation method according to claim 1, characterized in that: In step (1), the neodymium iron boron alloy sheet is subjected to hydrogen absorption under the first hydrogen pressure in the furnace, wherein the first hydrogen pressure in the furnace is greater than 80 kPa and less than or equal to 130 kPa; the thickness of the neodymium iron boron alloy sheet is 0.18 to 0.42 mm; the dehydrogenation temperature is 520 to 650 °C; and the vacuum degree in the furnace after dehydrogenation is less than or equal to 100 Pa. In step (2), the initial coarse powder is re-absorbed with hydrogen under the second hydrogen pressure in the furnace, wherein the second hydrogen pressure in the furnace is greater than 50 kPa and less than or equal to 80 kPa; the vacuum degree in the furnace during re-absorption of hydrogen is less than or equal to 1500 Pa.

3. The preparation method according to claim 1, characterized in that, The hydrogen content of the obtained NdFeB coarse powder is 1500-2150 ppm; the particle size of the obtained NdFeB coarse powder is 100-1500 μm.

4. The preparation method according to claim 1, characterized in that, The neodymium iron boron alloy sheet is obtained by melting and spinning various raw materials, and the composition of the neodymium iron boron alloy sheet is RE x M y B z Fe bal RE is selected from one or more of La, Pr, Nd, Y, Ho, Dy, Gd, Tb, and Er, and must contain Nd; M is selected from one or more of Co, Al, Cu, Zr, Ga, Nb, Ta, and Ti. Where x, y, and z represent the weight parts of RE, M, and B, respectively, and bal represents the balance, which consists of Fe and unavoidable impurities; based on 100 parts by weight of NdFeB alloy sheet, 28≤x≤35, 0.75≤y≤1.1, and 0.8≤z≤1.

1.

5. A type of NdFeB coarse powder, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 4.

6. The use of NdFeB coarse powder prepared by any one of claims 1 to 4, or NdFeB coarse powder according to claim 5, in improving the remanence and / or coercivity of NdFeB permanent magnets.

7. A method for preparing a neodymium iron boron permanent magnet, characterized in that, Includes the following steps: 1) The NdFeB coarse powder according to claim 5 is subjected to an air jet mill to obtain NdFeB fine powder; 2) The NdFeB fine powder is pressed in an orientation magnetic field to obtain a NdFeB compact; 3) Sinter and age the NdFeB compact to obtain sintered NdFeB magnets; 4) The sintered NdFeB magnets are infiltrated with Tb or Dy to obtain NdFeB permanent magnets.

8. The preparation method according to claim 7, characterized in that, The specific steps include the following: 1) Under a protective atmosphere, the NdFeB coarse powder according to claim 5 is mixed with an antioxidant and then subjected to an air jet mill to obtain NdFeB fine powder; wherein, the amount of the antioxidant is 0.08-0.25% of the mass of the NdFeB coarse powder; the air jet mill speed is 178-244 kg / h; and the average particle size D of the NdFeB fine powder is... 50 It is 2–5 μm; 2) Stir the NdFeB fine powder and lubricant through a 60-150 mesh sieve to obtain a mixture; wherein, the amount of lubricant is 0.05-0.3% of the mass of the NdFeB fine powder; press the mixture under a magnetic field strength of 1.5-3T to obtain a NdFeB compact; 3) Sinter the NdFeB compact at 1050-1090℃ for 3-8 hours, and then sinter at 1060-1080℃ for 2-12 hours to obtain a sintered body; subject the sintered body to two-stage aging treatment to obtain a sintered NdFeB magnet.

9. The preparation method according to claim 8, characterized in that, In step 3), the first-stage aging temperature is 720–950℃, and the first-stage aging time is 1–6 hours; the second-stage aging temperature is 450–600℃, and the second-stage aging time is 1–6 hours. In step 4), Tb or Dy is screen-printed onto the surface of the sintered NdFeB magnet, then infiltrated at 800–1000°C for 10–20 h, and then aged at 400–600°C for 5–15 h to obtain the NdFeB permanent magnet.

10. A neodymium iron boron permanent magnet prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Hydrogen decrepitation method of neodymium-iron-boron alloy and preparation method of neodymium-iron-boron magnet

    CN114284020A

  • Preparation method of high-remanence neodymium-iron-boron magnet

    CN119132820A

  • Low-carbon high-purity neodymium-iron-boron magnet and preparation method thereof

    CN121460321A